Цифрове телебачення в Україні: стан і перспективи розвитку - Федорчук, Людмила Петрівна (Київський національний університет імені Тараса Шевченка, 2016)
Метою дослідження є аналіз особливостей переходу ефірного телебачення України на цифровий формат. Застосовані такі методи дослідження: аналіз (для виділення суб’єктів процесу цифризації), історичний (для відтворення в хронологічній послідовності процесу переходу на цифровий телевізійний сигнал в Україні і світі), аналогія (для визначення перспектив). У результаті дослідження встановлено, що основними проблемами на шляху до повного переходу до цифрового мовлення і відмови від аналогового сигналу є: конфлікт компетенцій задія- них державних органів, відсутність впливу на монополіста-постачальника, відсутність ліцензій на цифрове мовлення у багатьох регіональних і місцевих телекомпаній, обмежені фінансові можливості аудиторії, технічне забезпечення зони покриття цифрового сигналу. Цей комплекс проблем зумовлює неоднозначність сприйняття переходу на цифровий формат в межах вітчиз- няного телевізійного ринку, а також іміджеві втрати України на міжнародному рівні через невиконання угоди «Женева 2006». Значимість дослідження полягає у виявленні нових взаємозв’язків і закономірностей у процесі переходу ефірного телевізійного мовлення на цифровий формат.

The main objective of the study was to analyse the particularities of transition from terrestrial to digital format of the television in Ukraine. This objective was accomplished with the help of the following research methods: the method of analysis was applied to select the subjects of digitalization and to determine their role in the overall process; historical method was used to recon- struct the chronological order of events in transition to the digital television in Ukraine and in the world; the method of analogy was applied to determine the prospects of digital broadcasting development in Ukraine. Results and Conclusions. The process of transition from analogue to digital format of television in Ukraine has been lasting for 10 years. This is due to some problems at the state level (the conflict in competences of the responsible state agencies, the lack of a single decision-making centre, the lack of influence on the monopoly provider), at the TV content market (the unfounded costs of territory coverage with analogue signal, the lack of digital broadcasting licenses for many regional and local channels), and at the service provider’s level (the monopoly position of the existing provider, the absence of grounded calculation for territory coverage by the current national network). This set of problems leads to ambiguity in digital television perception within the domestic market, and costs Ukraine in its international public image due to failure to fulfil the Geneva 2006 agreement. The new relationships and patterns in transition from terrestrial to digital format of the television broadcasting in Ukraine were discovered in this study. It is grounded that the coordinated and efficient work of responsible state agencies is needed to solve the existing problems and to implement transition to digital broadcasting in Ukraine. The construction of alternative digital networks and the licensing of new digital networks providers are also needed, as well as the state assistance in providing digital TV devices to vulnerable groups of population and proper information campaign of the need to transit to digital TV.
Digital Television in Ukraine: Current State and Prospects of Development
Keywords: digital television; analogue broadcasting; DVB-T2; Geneva 2006 agreement; National Council of Television and Radio Broadcasting of Ukraine; цифрове телебачення; аналогове мовлення; формат DVB-T2; угода «Женева 2006»; Національна рада України з питань телебачення і радіомовлення